REDESIGN THE PATTERN OF MAHRAM RELATION AMONG FAMILY MEMBER OF COASTAL POOR COMMUNITY; The Protection Measures of the intensively of Incest Behavior in Indonesia - Muhammad Hidayat; Nurcahaya Nurcahaya (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
This study describes the incest situation in three coastal Cities of Indonesia; Tanjung Balai, North Sumatra, Batam city Riau Archipelago, and North Jakarta, DKI Jakarta. The study background is since the high frequency of incest marriage in Indonesia. Instead of father, mother, uncle or brother take care of their biological family, they become the actors who want to marry their own blood family. The protection to the family is interpreted wrongly by marrying. On the other hand, Islam has regulated marriage rule in detail. The marriage is forbidden if the actors have blood relationship “Mahram relation”. The research method is a qualitative method in which the subject of the research is from various different background of organizations, data collecting technique and analysis are discussed. Marriage theories in Islam included in Alquran and hadist are also discussed. The finding of the research shows that the incest can be happen in the family because of wrong intensive communication factors, mis-interpretation of loyalty and protection, relationship domination, and economic factors. The design of the house is also as one determinant factors of incest, as the impact of poverty of the family. This study recommends government, family, and community to conduct reproductive education, religious education, re-design family relation and to increase income generating of the family in order they can have appropriate home to prevent the potency of incest. Keywords: Incest, coastal community, Mahram relation, poverty